Green Human Resource Management and Sustainable Development: A Systematic Exploration - Kusnawan, Agus; Setyani Dwi Lestari; Slamet Mudjijah (LP3kM Buddhi Dharma University, 2026)
This study examines the development of Green Human Resource Management (GHRM) research within sustainable development literature through bibliometric analysis. As a strategic human resource management approach, GHRM has received growing scholarly attention because of its contribution to promoting environmentally responsible behavior, strengthening organizational sustainability capabilities, and supporting long-term environmental performance. Nevertheless, systematic studies that map the evolution, thematic direction, and intellectual structure of this research field remain limited. Data were retrieved from the Scopus database, resulting in 76 open-access articles published between 2016 and 2024. The analysis was conducted using Biblioshiny to identify publication trends, dominant research themes, influential journals, and leading contributors. The findings reveal substantial publication growth after 2020, indicating increasing academic interest in GHRM and sustainability. Dominant themes include environmental performance, pro-environmental behavior, green HR practices, and sustainability-oriented organizational capabilities. Sustainability and the Journal of Cleaner Production emerged as the most influential journals, while Jabbour and Renwick were identified as key contributors. Overall, this study highlights GHRM’s shift toward broader sustainability and capability-based perspectives.